2021
DOI: 10.1097/shk.0000000000001864
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Sepsis Phenotypes on Mortality and Fluid Status in Critically Ill Patients

Abstract: Background: Sepsis is associated with high rates of in-hospital mortality, despite being the focus of medical research and public health initiatives for several years. The primary objective of this study was to determine the influence of septic phenotypes on rates of in-hospital mortality throughout intensive care unit (ICU) admission. Patients and Methods: Retrospective, single-center cohort study. Medical ICU of an academic medical center. Medical ICU patients admitted between January 2016 and August 2019 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, sepsis is an acquired disease and other variables contribute to the presentation, clinical course, and eventual outcome. Included in those variables are the type of infection and its primary source (20,26,27). Thus, to assess the contribution of this variable to the genetic host response, we performed whole transcriptomic sequencing in paired human samples of blood exposed to either HKEC or HKSA, two of the most common pathogens in sepsis and sepsis-related mortalities (20,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, sepsis is an acquired disease and other variables contribute to the presentation, clinical course, and eventual outcome. Included in those variables are the type of infection and its primary source (20,26,27). Thus, to assess the contribution of this variable to the genetic host response, we performed whole transcriptomic sequencing in paired human samples of blood exposed to either HKEC or HKSA, two of the most common pathogens in sepsis and sepsis-related mortalities (20,28).…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, sepsis is a life-threatening organ dysfunction rooted in a dysregulated host response to infection. 21 A literature review conducted by Lehnhardt et al reported fatality in five of 13 patients who developed sepsis following liposuction. 22 Vongpaisarnsin et al presented a death following cosmetic liposuction because of Pseudomonas aeruginosa septicemia, and he proposed that if we want to better deal with such a fatal complication, hygienic standards in addition to rigorous surgical staff training for handling surgical instruments become the necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, definition of sepsis was modified in 2016 to emphasize the critical presence of organ failure (30), while a modification of definition of ARDS was recently proposed (31). Both syndromes are perceived as heterogeneous entities with distinct phenotypes (32,33).…”
Section: Discussionmentioning
confidence: 99%